The Role of Digital Service Development by BUMDes Kuala Dua in Enhancing the Local Economy - Fatimah, Siti; Fahmi, Fahmi -; Kusumo Santoso, Radityo; Anantri, Feriska Ajeng (UI Scholars Hub, 2026)
Digital transformation has become an important instrument for strengthening local economies in rural areas, particularly through the role of village economic institutions. Village Owned Enterprises (BUMDes) hold a strategic position in integrating digitalization into business management and community empowerment. This study aims to analyze the role of BUMDes Kuala Dua in the development of digital services as a strategy for enhancing the local economy and to formulate a model for strengthening village-based digital economic institutions. The study employs a qualitative approach using a descriptive analytical method. Data were collected through in-depth interviews, participatory observation, and document analysis involving the management and business units of BUMDes Kuala Dua. Data analysis was conducted using the interactive model proposed by Miles and Huberman, complemented by SWOT analysis. The findings indicate that BUMDes Kuala Dua functions as a facilitator and a networking hub for rural economic digitalization through the development of promotional services and digital content production integrated with other business units. Digitalization contributes to expanded market access, improved promotional efficiency, job creation for young people, and the enhancement of digital literacy and entrepreneurial capacity within the village community. The successful implementation of digitalization is supported by innovative leadership and strong social capital; however, it continues to face structural constraints, including limited infrastructure, funding, and integration with village development programs. This study confirms that rural digitalization is more effective when positioned as an institutional and social process integrated into local economic development strategies.